Effects of fiber orientation angles of fiber-reinforced plastic on sand solid particle erosion behaviors. (19th December 2016) - Bao, Limin; Kameel, Hijjazulkifli; Kemmochi, Kiyoshi
Abstract : Solid particle erosion in industrial applications has been a serious problem in many engineering fields. Earlier studies on fiber-reinforced plastic (FRP) composites were mainly focusing on the erosive wear behavior at several different impact angles. However, the effect of fiber orientation on FRP composites has not been thoroughly investigated. Since fiber orientation is one of the important factors in which causing erosive wear damages to FRP composites, in order to understand the virtue of this problem, it is important to investigate the effect of fiber orientation at different impact angles. In this research, the effect of fiber orientation of unidirectional fiber-reinforced plastic composites on erosive wear behavior was studied. Sandblasting-type erosion tests were conducted on the FRP composites with fiber orientation ranging at three impact angles to clarify the relation between fiber orientation and erosive wear behavior. The Dyneema fiber (ductile material) and the carbon fiber (brittle material) were used for the reinforcement fiber in FRP. From the result, it is confirmed that CFRP composites with higher fiber orientation angle erode faster than the composites with lower fiber orientation angle. But the erosion characteristic of DFRP was almost the same regardless of the fiber orientation angle. The damaged surfaces of the FRP composites were then analyzed using scanning electron microscopy and the possible erosion wear mechanisms were investigated.